The Nationalization of Legislative Collaboration: Territory, Partisanship, and Policymaking in Argentina - Calvo, Ernesto; Leiras, Marcelo (Revista Ibero-Americana de Estudos Legislativos, 2012)
This paper analyzes the nationalization of collaborative policy efforts among lawmakers in Argentina. In doing so, we distinguish the nationalization of electoral competition and the nationalization of a legislator’s policy intent. To measure the nationalization of legislative efforts, we assess the degree to which legislators collaborate with members of their party and members of their district in the drafting of legislative initiatives. We interpret the density of cosponsorship networks as indicative of legislative collaboration among legislators and estimate exponential random graph models (ERGM) to explain the partisan and territorial determinants of collaboration over a 25-year period. A study of 130,000 legislative initiatives proposed to the Argentine Congress from 1984 to 2007 shows district and partisan effects becoming more prominent over time. We also show that district and partisan effects are more pronounced at higher thresholds of cosponsorship collaboration.